Implementasi Akuntansi Karbon dalam Kebijakan Fiskal Hijau di Indonesia: Kajian Scoping Review - Amrie Firmansyah (Politeknik Keuangan Negara STAN, 2025)
Research objective: This study aims to analyze the extent to which Indonesia's fiscal policy has incorporated carbon accounting principles within the public accounting system and green fiscal governance. Method: The study employs a scoping review approach, examining legal documents, fiscal policies, institutional reports, and international references related to the management of carbon economic value. Data were analyzed qualitatively and thematically to map the relationship between fiscal policy, public accounting systems, and carbon economic mechanisms in Indonesia. Research findings: The results indicate that Indonesia's legal and institutional frameworks have supported the implementation of carbon-based fiscal instruments; however, the integration between fiscal reporting systems and environmental data remains limited. Practical implication: The study provides recommendations for the Ministry of Finance, the Ministry of Environment and Forestry, and Bappenas to strengthen institutional coordination and integrate fiscal reporting with carbon-related information.